Ontogeny of copulatory behaviour in male Japanese quail classified by their T-maze performance as hatchlings - Lábaque, María Carla (2008)
This study examines the time courses of male mating behaviours using quail that were categorised at 2 d of age as high performance (HP) or low performance (LP) individuals in a T-maze. Individually caged males from each T-maze category were observed for 5 min after a female of the same category (HP or LP) was introduced into their home cages as a sexual partner at 4, 5, 6, 8, 10 and 12 weeks of age. The number of grabs, mounts and cloacal contacts performed by each male and his copulatory efficiency (number of cloacal contacts/number of grabs; CE) were determined at each time interval. No differences were observed in the proportion of HP and LP males performing grabs at any of the ages evaluated. However, a greater proportion of HP males showed mounting and cloacal contact behaviour, coupled with a higher CE than did their LP counterparts at 5 and 6, 6 and 8, and 8 weeks of age, respectively. At those ages, a higher mean number of mounts and cloacal contacts were also observed. No significant sexual behaviour differences between HP and LP quail were observed at 10 and 12 weeks of age. The results suggest that rapid negotiation of the T-maze in hatchlings is associated with accelerated puberty in male quail. The differential reproductive behaviour of HP males during the development of puberty does not remain extant in fully developed quail. The finding of accelerated male developmental sexual activity responses in HP quail indicates that selection for T-maze HP behaviour may allow males to be successfully bred at an earlier age.